Disseminated Histoplasmosis in a Patient with Advanced HIV Disease - Lessons Learnt from Bangladesh - Pervez, Md Mostaq; Cobb, Brian; Matin, Nashaba; Shahrin, Lubaba; Ford, Evelyn R; Pietroni, Mark (Journal of Health, Population and Nutrition, 2010)
Histoplasmosis is a systemic fungal disease, also known as Darling’s disease, caused by the dimorphic fungus Histoplasma capsulatum. It is usually self-limiting or localized in immunecompetent individuals whereas in patients with acquired immune deficiency syndrome (AIDS), it occurs in the disseminated form in 95% of cases. Although histoplasmosis predominates in the Americas (United States and Latin America, including Brazil) as an important infection among AIDS patients, it is not common in Bangladesh. In contrast, tuberculosis is extremely common in Bangladesh, with an estimated prevalence of 387 per 100,000 people. Here, a confirmed case of disseminated histoplasmosis is reported in Bangladesh in a known HIV-positive patient, which was initially suspected to be extrapulmonary tuberculosis. Key words: Case studies; Histoplasma capsulatum; Histoplasmosis; HIV; Tuberculosis; Bangladesh DOI: 10.3329/jhpn.v28i3.5561 J HEALTH POPUL NUTR 2010 Jun;28(3):305-307